(untitled) (Research, Society and Development, 2020)
Despite placing itself as a protagonist in important moments for the construction of the history of Brazil, the term youth is inserted in the Federal Constitution only in 2010 through constitutional amendment No. 65. Thus, the objective of the present study is to ascertain the existence of Public Policies for Youth in the municipality of Picos-PI and to promote a debate on the rights guaranteed by the Youth Statute. past 20 years. In public policies, existing in Picos-PI, we can observe some communication difficulties between young people and the Coordination, since the disclosures of the projects happen effectively only with the pre-university entrance exam, the other achievements have less scope. It is relevant that these public policies were not restricted to a specific class, since the Youth Statute guarantees the right to all young people, the dialogue could become closer with the realization of some research or conference to know the demands from from the young man’s point of view.